Data manipulation with R and SQL : building effective, coherent, and streamlined data structures - Grogan, Michael (O'Reilly, 2018)
"R is the tool of choice for the business analyst faced with the daunting task of analyzing huge datasets. Unlike traditional analysis tools like Excel, R offers the flexibility to structure large datasets in a manner suitable for robust analysis. It also provides the speed and capacity necessary to run computations in a fast and efficient manner. This video teaches you how to use R and SQL to manipulate densely populated datasets for business analytics. You'll learn how to connect R to a SQL database, import data, commit queries from R, and how to replicate Excel functions like VLOOKUP and SUMIF to conduct advanced manipulation methods. Participants should be familiar with SQL databases and have some prior experience manipulating databases using Excel type software."--Resource description page